Much room for change: access to surgical care for stateless individuals in Pakistan - Humza Thobani; Mashal Murad Shah; Anam N Ehsan; Sadaf Khan (Globalization and Health, 2023)
Abstract Background As developing countries take steps towards providing universal essential surgery, ensuring the equitable distribution of such care for underrepresented populations is a vital function of the global surgery community. Unfortunately, in the context of the global “stateless”, there remains much room for improvement. Key issues Inherent structural deficiencies, such as lack of adequate population data on stateless communities, absent health coverage policies for stateless individuals, and minimal patient-reported qualitative data on barriers to surgical service delivery prevent stateless individuals from receiving the care they require – even when healthcare infrastructure to provide such care exists. The authors therefore propose more research and targeted interventions to address the systemic issues that prevent stateless individuals from accessing surgical care. Conclusion It is essential to address the aforementioned barriers in order to improve stateless populations’ access to surgical care. Rigorous empirical and qualitative research provides an important avenue through which these structural issues may be addressed.